Molecular Interaction Study of Binary Liquid Solution Using Ultrasonic Technique - Panda, Subhraraj (Recent Innovations in Chemical Engineering, 2022)
Aim: The major goal of this fascinating study was to determine the molecular interaction of the polymer dextran with urea in an aqueous media using a more straightforward technique. Background: Many physical approaches play important roles in identifying the molecular structure and molecular characteristics of various solutions. In recent years, advances in ultrasonic methods have become a potent tool for assessing information regarding the physical and chemical behaviour of liquid molecules. Objective: The acoustical parameters like “free volume, internal pressure, absorption coefficient, Rao’s constant, and Wada’s” constant are evaluated from the measured data. The significance gives subjective information on the type and quality of solute-solvent particle interactions in liquid solutions. Methods: Specific gravity bottles, Ostwald's viscometer, and multifrequency ultrasonic interferometer were used to determine the density (ρ), viscosity (η), and ultrasonic speed (U) in binary systems of biopolymer dextran with urea at 313 K. Results: After thoroughly examining the results, a careful study of the findings revealed the link between the solute and the solvent. In the light of solute-solvent and solutesolute interactions, the fluctuation of these parameters with a change in dextran concentration and frequency has been examined. Conclusion: The thermo-acoustic value indicates an atomic interaction in the solution. In the current systems, extremely weak molecular interactions such as solute-solvent, solute- solute, etc., are commonly seen. The structure largely determines the force and type of contact.
Keywords: specific gravity bottles